Fatty acid synthesis suppresses dietary polyunsaturated fatty acid use - Worthmann, Anna; Ridder, Julius; Piel, Sharlaine Y. L.; Evangelakos, Ioannis; Musfeldt, Melina; Voß, Hannah; O’Farrell, Marie; Fischer, Alexander W.; Adak, Sangeeta; Sundd, Monica; Siffeti, Hasibullah; Haumann, Friederike; et al. (Nature Communications, 2024)
Dietary polyunsaturated fatty acids (PUFA) are increasingly recognized for their health benefits, whereas a high production of endogenous fatty acids - a process called de novo lipogenesis (DNL) - is closely linked to metabolic diseases. Determinants of PUFA incorporation into complex lipids are insufficiently understood and may influence the onset and progression of metabolic diseases. Here we show that fatty acid synthase (FASN), the key enzyme of DNL, critically determines the use of dietary PUFA in mice and humans. Moreover, the combination of FASN inhibition and PUFA-supplementation decreases liver triacylglycerols (TAG) in mice fed with high-fat diet. Mechanistically, FASN inhibition causes higher PUFA uptake via the lysophosphatidylcholine transporter MFSD2A, and a diacylglycerol O-acyltransferase 2 (DGAT2)-dependent incorporation of PUFA into TAG. Overall, the outcome of PUFA supplementation may depend on the degree of endogenous DNL and combining PUFA supplementation and FASN inhibition might be a promising approach to target metabolic disease.